Experimental evaluation of water surface profiles upstream and downstream of a culvert with and without an apron - Soroush Jafari; Mohammad Vaghefi; Amin Mahmoudi (Results in Engineering)
Culverts are structures designed to facilitate the transfer of water beneath roadways, effectively connecting two areas within a catchment. Several critical parameters influence the design of a culvert and its surrounding environment. Among these, the flow conditions and the management of water levels at both the inlet and outlet are essential for the culvert's operation, particularly regarding its performance during flood events. This article examines the impact of variations in the longitudinal slope of the culvert and the elevation of the downstream bed—both with and without an apron—on the flow profile entering and exiting the culvert. To investigate this, a series of 80 experiments were conducted in a straight laboratory channel under steady flow conditions. The objective of these tests is to analyze the water level profiles both upstream and downstream of the culvert under various scenarios. The results indicated that increasing the culvert slope led to a rise in water level on the upstream side of the culvert. Specifically, the maximum water level upstream increased by 14 %, 56 %, and 65.1 % when the culvert slope was raised from zero to 2.5 %, 4 %, and 5.5 %, respectively. Additionally, the minimum water level upstream also increased by 19.1 %, 70.6 %, and 83.1 % under the same slope changes. The average maximum and minimum water levels for all scenarios were calculated and compared. The findings of this research will be valuable for analyzing water transfer both upstream and downstream of the culvert structure, as well as for enhancing hydraulic c alculations related to its performance.